2013
DOI: 10.3390/ijerph10052028
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Individual Correlates of Various Types of Physical Activity among Community-Dwelling Middle-Aged and Elderly Japanese

Abstract: Recent studies have suggested the importance of the neighborhood environment in determining the specific type of physical activity. However, few studies on this topic have been undertaken in Japan. This study examined the association of three types of physical activity and their associations with individual and neighborhood environmental factors among middle-aged and elderly Japanese. Participants were 2,449 adults aged 40–69 living in Fujisawa city who had undergone health checkups and responded to our survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
1
30
5
1
Order By: Relevance
“…This study controls for older residents’ personal characteristics (e.g., age, gender, marital status and ethnicity) because evidence shows that people’s personal characteristics affect their walking levels [44,45,46]. …”
Section: Introductionmentioning
confidence: 99%
“…This study controls for older residents’ personal characteristics (e.g., age, gender, marital status and ethnicity) because evidence shows that people’s personal characteristics affect their walking levels [44,45,46]. …”
Section: Introductionmentioning
confidence: 99%
“…This variable was composed of four items based on the International Physical Activity Questionnaire for the Elderly (Inoue et al, 2009a(Inoue et al, , 2009b. We added 11 items (seven core and four recommended items) from the module (17 items) to the questionnaire, based on a study by Saito et al (2013). To score each item, we followed the system that they used.…”
Section: Physical Activity Environmentmentioning
confidence: 99%
“…In Western countries, various studies have examined differences in the levels of exercise and PA resulting from differences in socio-economic status (SES); persons with low SES are less likely to exercise and be physically active, even if the outcomes are somehow distinguished by the type of exercise and PA being measured (Blair, 1988;Gidlow et al, 2006;Beenackers et al, 2012). Studies conducted in Asian Pacific countries, such as Taiwan and China (Lee et al, 2007;Chen et al, 2015;Lin et al, 2016), Australia (Eime et al, 2015) and Japan (Anzai et al, 2000;Fukuda et al, 2005;Saito et al, 2013) support the notion that in those regions, SES differences impact levels of both exercise and PA. Although there have been a few studies on older adults in regard to this matter (Walsh et al, 2001;Chad et al, 2005;Hillsdon et al, 2008;Ashe et al, 2009;Browning et al, 2009;Haley and Andel, 2010;Yamakita et al, 2015), these have also found SES differences to impact on levels of both exercise and PA in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhood social norms for RW can widen an individual's intention-behavior gap. Recent studies on walking behavior (Ball et al, 2007;Ball, Jeffery, Abbott, McNaughton, & Crawford, 2010;Granner, Sharpe, Hutto, Wilcox, & Addy, 2007;McNeill, Kreuter, & Subramanian, 2006;Saito, Oguma, Inoue, Tanaka, & Kobori, 2013;Van Cauwenberg et al, 2011) reported that neighborhood social factors (i.e. social cohesion, social capital, deprivation, and safety) were important relevant determinants in addition to individual psychological factors (i.e.…”
Section: Introductionmentioning
confidence: 99%